Solvent-free directed patterning of a highly ordered liquid crystalline organic semiconductor via template-assisted self-assembly for organic transistors - Kim, Aryeon (Advanced materials (Deerfield Beach, Fla.), 2013)
© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.